A case for developing the emotional capacities of social workers: A commentary on “Promoting self-awareness: Infant observation training as a model” - Bliss, S (Smith College Studies in Social Work, 2005)
tex.unique-id: ISI:000232698200005
Keywords: dept.swk; ⚠️ Invalid DOI

Micro ruptures and repairs in the beginning phase of cross-cultural psychotherapy - Keenan, Elizabeth; Tsang, A.; Bogo, Marion; George, Usha (Clinical Social Work Journal, 2005)
The article discusses misunderstandings and misattunements that occur in the beginning phase of cross-cultural psychotherapy. Sources of micro ruptures are outlined, including client maladaptive patterns, therapist misunderstandings, cross-cultural misunderstandings due to cultural variations, and asymmetrical power relations involving the impact of prior experiences or current therapy practices. Multiple clinical vignettes illustrate the rupture/repair process, drawing on Safran and Muran's (2000) list of direct and indirect techniques., (C)2005 Kluwer Academic Publishers
12 citations (Crossref) [2023-10-31] Place: (C)2005 Kluwer Academic Publishers
Keywords: Beginning phase of psychotherapy; Cross-cultural psychotherapy; Rupture and repair; Therapeutic relationship; beginning phase of psychotherapy; cross-cultural psychotherapy; dept.swk; rupture and repair; therapeutic relationship